الأمير عبد القادر حياته و دعوته - الزاوي فرحات, الزهرة (University of Eloued جامعة الوادي, 2018)
"هدفت هذه الدراسة إبراز حياة الأمير عبد القادر ودعوته. إذ يعتبر الأمير عبد القادر من الشخصيات العظيمة التي تركت أثرا عظيم في تاريخ المقاومة الجزائرية، وكذلك كان للأمير عبد القادر دورا بالغا في الجانب الدعوي إضافة إلى العمل الجهادي العسكري، فقد عمل على توعية الشعب الجزائري من خلال تطبيق أسس إسلامية في دعوته إلى الله. تطرقنا في دراستنا هذه إلى سيرة الأمير عبد القادر وكذلك إلى معالم المنهج الدعوي عند الأمير عبد القادر. وبعد الدراسة العميقة لحياة الأمير عبد القادر وسيرته الجهادية الكبرى، توصلنا إلى أنه كان للأمير عبد القادر دورا كبيرا وفاعلا في مجال العمل الدعوي في فترة تأسيسه للدولة الجزائرية الحديثة، إضافة إلى تركيزه على العمل الدعوي تماشيا مع العمل العسكري الجهادي. " "The main purpose of this research is to elaborate to what extent does Al-Amir Abdelkader focused on Islamic Advocacy working at the same time of his Military Resistance working. In this research, we have collected the data from many last researches and references that has been focused on the life and history of Amir Abdelkader. And we have analyzed the references information in order to reach the desired results of this research. By analyzing and reviewing the data and information from many references that have focused on the history and Military life of Al-Amir Abdelkader, we have obtained the following results: 1. by looking to the biggest history of Al-Amir Abdelkader we can conclude that he had a huge impact on his followers by leading them to the right way of Islam. 2. Al-Amir Abdelkader had established his first state of Algeria by using principle of The holy Quran and Sunnah in his first constitution. 3. Al-Amir Abdelkader had concentrated on Islamic Advocacy working in his beginning leadership of life, because he was prince of Advocacy more than Military leader"
مذكرة ماستر تخصص دعوة واعلام
Keywords: الأمير - عبد القادر - حياته - دعوته; Prince - Abdelkader - sa vie - son appel